Traditional Economy Influences on Intellectual Capital Development - Evgeny Popov; Maxim Vlasov; Horst Hanusch (Montenegrin Journal of Economics)
During econometric analysis conducted by the authors the following hypotheses were substantiated. First of all we found the most pronounced correlation between the amount of innovative products, works and services in the total amount of shipped goods, performed activities and technological innovation costs per one person. This demonstrates the need for planning and implementing state programs on raising intellectual capital in multicultural regions with traditional economics.